Growth and productivity of stevia variety Cibodas Manis 3 (Stevia rebaudiana) in 40 days planting with agroforestry - MILA NADIA CHOERIAH; NURHENI WIJAYANTO; IRMANIDA BATUBARA (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Choeriah MN, Wijayanto N, Batubara I. 2024. Growth and productivity of stevia variety Cibodas Manis 3 (Stevia rebaudiana) in 40 days planting with agroforestry. Biodiversitas 25: 3277-3283. Stevia (Stevia rebaudiana Bertoni.) is a shrub plant that can be used as a substitute for sugar cane and has the potential to be cultivated in agroforestry ways. This study aims to analyze the growth and productivity of stevia in agroforestry systems compared to monocultures. Stevia was planted in 2 types of land, namely agroforestry and monoculture. The research location's soil and area's climatic conditions were observed stevia agroforestry was grown under pine, eucalyptus, and coffee trees. During stevia planting, the height was measured. Stevia was harvested 40 days after planting, and leaf area, number of leaves, leaf weight, and harvest productivity were measured. In addition, chlorophyll and stevioside yields were analyzed using UV VIS and LC-MS/MS spectrometry. Stevia in agroforestry land had higher chlorophyll and stevioside content than monoculture, although not as good as stevia in monoculture, which had higher height, number of leaves, leaf area, wet weight, dry weight, and productivity compared to agroforestry. The total stevioside produced from agroforestry land was 1.63 kg/ha, while it was 2.19 kg/ha from monoculture land. Stevia in agroforestry land also has a higher secondary metabolite content than in monoculture. This is related to the growing conditions that stress stevia. Pearson correlation test results also show a relationship between the amount of chlorophyll and the stevioside content in stevia plants.